Effects of structural environmental enrichment on welfare of juvenile seabream (Sparus aurata) - Arechavala Lopez, Pablo (2020)
Current production systems of finfish aquaculture, and in particular intensive farming systems, can cause welfare problems leading not only to poor condition of the fish but also to a decrease in product quality. Adding structural environmental enrichment (EE) to bare rearing environments may improve the welfare of certain cultured fish. In this study we experimentally demonstrate the positive effects of adding structural EE on rearing environments of juvenile seabream (Sparus aurata). Fish maintained for 35 days with EE showed less aggression and interactions with the net pen, and lower erosion of pectoral and caudal fins, compared to fish kept in bare conditions (non-enriched, NE). In addition, EE modified the horizontal distribution of fish in the experimental cage, increasing the use of the inner areas. Non-significant effects of EE were observed on fish body condition and growth, and on brain monoamines levels and mortality. Nevertheless, this work highlights the potential use of structural EE to improve welfare of juvenile seabream, which might be feasible to apply at larger-commercial scale.